Sensory data analysis crushed tomatoes with fuzzy logic and multivariate techniques - Césari, Matilde Inés; Ventrera, Nancy Beatriz; Gámbaro, Adriana (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2018)
All data collection and analysis techniques, generated in the sensory evaluation, constitute a branch of the statistic called sensometry. If it is taking into account the vagueness and uncertainty with which human perceptions are manifested, the most appropriate strategy for obtaining precise knowledge from subjective evaluations is to transform the sensory data through fuzzy mathematics. However the potential of fuzzy reasoning, there are currently few references about the application of fuzzy logic in sensory evaluation, and there are no harmonized and systematized criteria and methods for objective sensory evaluation and reproducibly in plant foods. The results obtained in sensory tests of crushed tomato allowed to expose a methodological framework for the sensometric analysis of fuzzy data with the use of fuzzy logic and methods of multivariate analysis of data. In this way the techniques in the sensorial tests are optimized, and thus the process of sensorial analysis is renewed, developing a specific area that will improve the economic value in the Argentinean food production.